2021
DOI: 10.1215/00703370-9476273
|View full text |Cite
|
Sign up to set email alerts
|

The Fertility of Immigrants From Low-Fertility Settings: Adaptation in the Quantum and Tempo of Childbearing?

Abstract: Immigrant women who have lived longer in a destination often have relatively low levels of fertility, which is sometimes taken as evidence of the adaptation of behavior. This evidence is almost exclusively based on studies of immigrants from high-fertility settings, while the fertility of immigrants from low-fertility settings has been largely overlooked. Research has also rarely studied the fertility of immigrants who migrated as children, despite the methodological advantages of applying such an approach. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…First-generation migrants are not considered in our study. Their fertility depends largely on short-term influences related to their duration of residence in Sweden, which is challenging to consider in a study on period fertility trends (Andersson 2004;Mussino, Wilson, and Andersson 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First-generation migrants are not considered in our study. Their fertility depends largely on short-term influences related to their duration of residence in Sweden, which is challenging to consider in a study on period fertility trends (Andersson 2004;Mussino, Wilson, and Andersson 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Longer term differences, as well as the convergence of migrant to native fertility, are explained in terms of the adaptation hypothesis, a gradual process in which exposure to new social structures and ideas shifts one's preferences and behaviours toward those of the destination country (S. Goldstein & Goldstein, 1981). Previous research has found evidence of adaptation among migrant groups from high-fertility countries, decreasing their fertility over time (Andersson, 2004;Milewski, 2007), as well as among some migrant groups from low-fertility countries, increasing their fertility after some years after migration (Tønnessen & Mussino, 2020) when studying migrants from high-fertility countries, adaptation is difficult to reach because migrants may migrate already with a higher number of children than the norm at the destination (Mussino et al, 2021). In this respect, it has been claimed that migrants from lowfertility countries facilitate the testing of the adaptation 'from below', as they are less likely to already have children at the time of migration (Tønnessen & Mussino, 2020).…”
Section: Previous Theories On the Fertility Of Migrantsmentioning
confidence: 99%
“…Few studies have focused specifically on the fertility of migrants from low‐fertility countries, although these groups are less likely to have children before or around the time of migration (Tønnessen & Mussino, 2020) and have consequently been claimed to facilitate the testing of the adaptation ‘from below’ at net of the impact of interrelated demographic events. And these studies have shown contradictory results, finding evidence of adaptation to the reproductive behaviours of the receiving society among some groups (Hwang & Saenz, 1997; Lübke, 2015; Nahmias, 2004; Tønnessen & Mussino, 2020), but not among others (Mussino et al, 2021; Okun & Kagya, 2012). Moreover, the studies have looked primarily at a single migrant origin in a single destination, without including the country of origin in the analytical framework, despite migrant selectivity is likely to influence migrants’ fertility behaviours in terms of dissimilarities to the behaviour of stayers at origin and similarities to that of nonmigrants at destination (Lindstrom & Saucedo, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption perspective highlights that migration, especially when international, disrupts the life-course trajectories of individuals in a manner not experienced by non-migrants ( Bach 1981 ; Lindstrom and Giorguli Saucedo 2002 , 2007 ; Mussino, Wilson, and Andersson 2020 ). Migration often entails family separation, which might disrupt patterns of childbearing ( Andersson, Obucina, and Scott 2015 ; Boyle et al 2008 ; Chattopadhyay, White, and Debpuur 2006 ).…”
Section: Theoretical Background: Linking Ethno-racial and Nativity Di...mentioning
confidence: 99%